Strengthening Scaling of Fertiliser Recommendation Packages in Rwanda - Mudereri, B.T.; Kihoro, E.; Kihiu, E.; Kirui, L.; Benimana, G.U.; Cyamweshi, A.; Kayumba, J.; Gatari, E. (2025)
This report assesses the scaling readiness and use of fertilizer recommendation packages integrated into Rwanda’s Smart Nkunganire System (SNS). Building on participatory innovation packaging and scaling readiness exercises conducted in 2024 and 2025, the study examines technical, institutional, and user-level factors influencing adoption and performance. Findings show that SNS has transitioned from a transactional subsidy platform to a data-driven, advisory-enabled system with strong national reach, while highlighting remaining challenges related to inclusivity, system integration, last-mile delivery, and long-term sustainability. The report provides actionable recommendations to strengthen user-centred design, embed gender equality and social inclusion, and support responsible and sustainable scaling of digital fertilizer recommendations in Rwanda.